Pengaruh senam lansia terhadap derajat depresi pada lansia di panti werda - Kowel, Richard; Wungouw, Herlina I. S.; Doda, Vanda D. (Universitas Sam Ratulangi, 2016)
Abstract: Depression is a serious medical illness with mood, cognitive, and physical symptoms. Mood symptoms include depressed, sad, or irritable mood; loss of interest in usual activities; inability to experience pleasure; feelings of guilt or worthlessness; and thoughts of death or suicide. Cognitive symptoms include inability to concentrate and difficulty in making decisions. Physical symptoms include fatigue, lack of energy and changes in sleep, appetite, and activity levels. Geriatric depression is more severe than depression in other groups of age, where it causes depressive symptomps to 15% elderly. This study was carried out to identify the impact of Senam Lansia on the degree of depression in elderly. This is an experimental study that was conducted to 18 participants that live in Senja Cerah Hospice Manado. The degree of depression was assessed using Hamilton Depression Rating Scale. This 8-weeks senam-lansia-intervented study found a positively moderate and significant impact of Senam Lansia on the degree of depression in elderly (r = 0,594; p < 0,05). Futhermore, Senam Lansia has a positive impact on participants’ activities of daily living (ADL) such as increasing mobility and appetite, decreasing muscle fatigue, and developing positive feelings such as happy, healthy, fresh and fit.Keywords: elderly, depression, senam lansiaAbstrak: Depresi merupakan kondisi medis serius dengan gejala-gejala mood, kognitif dan fisik. Gejala-gejala mood termasuk depresi, sedih, dan mood irritable; kehilangan minat dalam aktivitas sehari-hari; ketidakmampuan untuk merasakan kesenangan; perasaan bersalah dan tidak berharga; dan ide-ide kematian dan bunuh diri. Gejala-gejala kognitif termasuk ketidakmampuan untuk berkonsentrasi dan kesulitan dalam dalam membuat keputusan. Gejala-gejala fisik termasuk kelelahan, kekurangan energi, dan perubahan tidur, nafsu makan, dan tingkat aktivitas. Depresi lansia lebih parah dibandingkan depresi pada grup usia lain, di mana depresi pada lansia memunculkan gejala depresi pada 15% lansia. Penelitian ini dilakukan untuk mengidentifikasi pengaruh Senam Lansia terhadap derajat depresi pada lansia. Penelitian eksperimental ini dilakukan pada 18 responden yang tinggal di Panti Werda Senja Cerah Manado. Derajat depresi dinilai menggunakan Hamilton Depression Rating Scale. Penelitian dengan intervensi Senam Lansia selama 8 minggu ini didapatkan bahwa Senam Lansia secara signifikan dan berkorelasi positif sedang dengan penurunan derajat depresi lansia (r = 0,594; p < 0,05). Selain itu, Senam Lansia mempunyai dampak positif pada Activities of Daily Living (ADL) seperti peningkatan mobilitas dan nafsu makan, penurunan kelelahan otot, dan perasaan senang, sehat, segar dan bugar.Kata kunci: lansia, depresi, senam lansia